Initial experience with a novel ePTFE-covered balloon expandable stent in patients with near-atretic or severe aortic coarctation and small femoral arterial access. (11th February 2021) - Al Balushi, Asim; Pascall, Emma; Jones, Matthew I.; Qureshi, Shakeel; Butera, Gianfranco
Abstract: Objectives: We report our experience of using the Bentley BeGraft Aortic stent in patients with severe or near-atretic aortic coarctation and small femoral arterial access. Background: Use of covered stent is recommended in some settings such as aortic coarctation with associated aneurysm, Turner syndrome, and coarctation with aortic atresia. However, currently available covered stents need larger sheaths that may limit their use in children and patients with smaller arterial access. Newer stents may overcome this limitation. Methods: Single-centre retrospective study of patients with severe or near-atretic aortic coarctation and small femoral arterial access. Results: Between July and October, 2019, five patients (median age 15 years) with near-atretic or severe coarctation were treated with a Bentley BeGraft Aortic stent. Long sheaths between 9 and 11 Fr were used to implant stents, which were dilated up to 12–16 mm. None of the patients had residual coarctation (gradient >20 mm of mercury) after stenting. None of the patients developed acute vascular injuries or local access related complications at the end of the procedure or during follow-up (range 6–10 months). Conclusions: Bentley BeGraft aortic stents are important to consider in patients with severe coarctation and provided acute procedural success in patients with small femoral arterial access and widen the applicability in this patient population.